Non-aqueous electrolyte secondary battery
By using composite oxides with high Ni content and low Co content in lithium-ion secondary batteries, and adding specific cations and oxalate complexes to the electrolyte, the capacity maintenance problem caused by instability of the composite oxide is solved, and the battery performance with high capacity and long life is achieved.
Patent Information
- Application Number
- CN202080059965.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-08-30
- Filing Date
- 2020-07-16
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2040-07-16
AI Technical Summary
In lithium-ion secondary batteries, when the cobalt content is reduced, the crystal structure of the composite oxide is prone to become unstable, resulting in a decrease in capacity maintenance.
A composite oxide containing lithium and transition metal is used as the positive electrode active material, where the atomic ratio of Ni is set to be more than 90%, the atomic ratio of Co is reduced to less than 10%, and a specific cation X and oxalate complex anion Y are added to the electrolyte to form a stable fluoride coating.
It effectively suppresses the reduction of capacity maintenance and improves the overall performance of the battery, especially in terms of high capacity and long life.
Smart Images

Figure CN114342120B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a nonaqueous electrolyte secondary battery. Background Art
[0002] Non-aqueous electrolyte secondary batteries, particularly lithium ion secondary batteries, have high voltage and high energy density and are therefore expected to be used as power sources for small consumer applications, power storage devices, and electric vehicles.
[0003] Patent Document 1 proposes a lithium ion secondary battery comprising lithium bis(fluorosulfonyl)imide (LiFSI) and lithium bis(oxalatoborate) (LiBOB), and states that the decrease in capacity and rate characteristics is suppressed by this.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2016-139610 Summary of the invention
[0007] As a positive electrode active material of a lithium ion secondary battery, a composite oxide containing lithium and a metal (particularly a transition metal) is used. As a composite oxide containing lithium and a transition metal, lithium cobalt oxide (LiCoO2) has been used conventionally.
[0008] On the other hand, in recent years, the price of cobalt has soared with the increase in demand, and it is expected to use a positive electrode active material that does not contain Co. From this perspective, attempts have been made to use a composite oxide in which the content ratio of Co is reduced by replacing a part of the metal constituting the composite oxide with other metal elements. Among them, lithium nickel composite oxides containing Ni as a transition metal are expected from the perspective of obtaining a high capacity.
[0009] However, when the Co content ratio decreases, the composite oxide containing lithium and a transition metal tends to change into a crystal structure in which lithium ions are difficult to be absorbed and released with repeated charge and discharge, and the capacity retention rate tends to decrease.
[0010] In view of the above, one aspect of the present disclosure relates to a non-aqueous electrolyte secondary battery, comprising: a positive electrode, a separator, a negative electrode sandwiching the separator and facing the positive electrode, and an electrolyte, wherein the positive electrode comprises a composite oxide, the composite oxide comprising lithium as a first metal, and a second metal other than lithium, in the composite oxide, the second metal comprises Ni, the proportion of Ni in the second metal is 90 atomic % or more, and the proportion of Co in the second metal is 10 atomic % or less, and the electrolyte comprises: a metal selected from Na + , K + , Rb +, Cs + , Fr + Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ , and Al 3+ At least one cation X and an oxalate complex anion Y in the group consisting of.
[0011] According to the present disclosure, in a non-aqueous electrolyte secondary battery using a composite oxide containing lithium and a transition metal, the content ratio of Co in the entire metal can be reduced and a decrease in the capacity retention rate can be suppressed. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 This is a perspective schematic diagram in which a part of the nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure is cut away. DETAILED DESCRIPTION
[0013] The non-aqueous electrolyte secondary battery of the embodiment of the present disclosure comprises: a positive electrode, a separator, a negative electrode sandwiching the separator and facing the positive electrode, and an electrolyte. The positive electrode comprises: a composite oxide containing lithium (a first metal) and a second metal other than lithium (hereinafter also referred to as a "lithium-containing composite oxide"). In the lithium-containing composite oxide, the second metal comprises Ni, the proportion of Ni in the second metal is 90 atomic % or more, and the proportion of Co in the second metal is 10 atomic % or less.
[0014] The nonaqueous electrolyte secondary battery uses a lithium-containing composite oxide, and the content of Co in the second metal is reduced to 10 atomic % or less. In addition, the second metal contains Ni and the content of Ni in the second metal is set to 90 atomic % or more, thereby achieving high capacity.
[0015] On the other hand, in a non-aqueous electrolyte secondary battery, the ion valence of Ni in the lithium-containing composite oxide changes with the absorption and release of lithium ions due to charge and discharge, and the crystal structure of the lithium-containing composite oxide tends to become unstable due to the change in the ion valence of Ni. In particular, when the content ratio of Co is less than 10 atomic %, the lithium-containing composite oxide tends to become (inactivated) a crystal structure in which reversible absorption and release of lithium ions are difficult due to repeated charge and discharge, and the capacity retention rate tends to decrease.
[0016] However, by making the electrolyte contain a + , K + , Rb + , Cs + , Fr + Mg 2+ , Ca 2+ , Sr2+ , Ba 2+ , and Al 3+ At least one cation X and an oxalate complex anion Y in the group consisting of the above can suppress a decrease in the capacity retention rate.
[0017] Non-aqueous electrolyte secondary batteries usually contain fluorine compounds in lithium salts (such as LiPF6, etc.) contained in the electrolyte, solvents (such as fluoroethylene carbonate (FEC), etc.), additives, or binders (such as polyvinylidene fluoride (PVdF), etc.) that may be contained in the positive and negative electrodes. By decomposing these fluorine compounds, a fluoride film containing cations X and fluorine can be formed on the surface of the lithium-containing composite oxide as the positive electrode (positive electrode active material). For example, when the cation X is a cesium ion, a film containing cesium fluoride CsF can be formed. It can be considered that the irreversible structural changes of the lithium-containing composite oxide caused by the side reaction with the electrolyte can be suppressed by the fluoride film. Therefore, it can be considered that the reduction of the capacity retention rate is suppressed.
[0018] It can be considered that the fluoride film exists in a state mixed with LiF and fluoride containing cation X. Since the ionic radius of cation X is different from that of lithium ions, there may be a gap around cation X in the fluoride film through which lithium ions can pass. Therefore, it can be considered that the fluoride film is not easy to become a resistance to the movement of lithium ions, and the capacity maintenance rate can be maintained at a high level. Among them, when the ionic radius of cation X is larger than that of lithium ions, the gap tends to become larger, and it is easy to maintain a higher capacity maintenance rate.
[0019] Furthermore, by including oxalate complex anion Y in the electrolyte, the decrease in capacity maintenance rate can be further suppressed. The oxalate complex anion Y is decomposed in the negative electrode to form a coating on the surface of the negative electrode active material. In addition, it can be considered that the oxalate complex anion Y (or its decomposition product) is attached to the fluoride coating on the surface of the positive electrode active material, or is incorporated into the fluoride coating to stabilize the fluoride coating. As a result, it is believed that a low and dense coating with low movement resistance of lithium ions is formed on the surface of the positive electrode active material, which can be considered to suppress excessive side reactions and further suppress the decrease in capacity maintenance rate. It should be noted that the above mechanism only represents the current views of the inventors, and the present invention is not limited to these.
[0020] The oxalate complex anion Y can be selected from B(C2O4)2 - 、BF2(C2O4) - 、P(C2O4)3 - PF2(C2O4)2 - , and PF4(C2O4) - At least one of the group consisting of.
[0021] The oxalate complex anion Y may contain fluorine. In this case, the fluoride component for forming the fluoride film can be supplied by the decomposition of the oxalate complex anion Y. Therefore, as the oxalate complex anion Y containing fluorine, it may also be BF2(C2O4). - , PF2(C2O4)2 - , and PF4(C2O4) - or at least any one of them.
[0022] For the cation X and the oxalate complex anion Y, their salts can be added to the electrolyte, or the salts of the cation X with other anions and the lithium salt of the oxalate complex anion Y can be added to the electrolyte.
[0023] The lithium-containing composite oxide may be a compound having a layered rock salt-type crystal structure containing lithium and a transition metal. The lithium-containing composite oxide contains at least nickel as the transition metal of the above-mentioned layered compound. In the lithium-containing composite oxide, the atomic fraction of nickel among the metal elements other than lithium is 0.9 or more. The atomic fraction of cobalt among the metal elements other than lithium is 0.1 or less. The atomic fraction of cobalt among the metal elements other than lithium may also be 0.05 or less.
[0024] Specifically, the lithium-containing composite oxide may also contain a material represented by the composition formula Li a Ni 1-x-y Co x M y O2. Among them, 0 < a ≤ 1.2, 0 ≤ x ≤ 0.1, 0 ≤ y ≤ 0.1, 0 < x + y ≤ 0.1. M is at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Cu, Zn, Al, Cr, Pb, Sb, and B, and among them, Al is preferred. It should be noted that the value of a representing the molar ratio of lithium increases or decreases due to charge and discharge. The cobalt ratio x can be 0 < x ≤ 0.05, or can be 0.01 ≤ x ≤ 0.05.
[0025] Next, the non-aqueous electrolyte secondary battery of the embodiment of the present disclosure will be described in detail. The non-aqueous electrolyte secondary battery includes, for example, an electrolyte, a negative electrode, and a positive electrode as follows.
[0026] [Electrolyte]
[0027] The electrolyte generally includes a non-aqueous solvent and a solute dissolved in the non-aqueous solvent. The solute may contain a lithium salt. The solute is an electrolyte salt that dissociates ions in the electrolyte. The components of the electrolyte other than the solvent and the solute are additives. Various additives may be included in the electrolyte. The cation X and the oxalate complex anion Y may be included in the electrolyte as additives.
[0028] As the non-aqueous solvent, for example, cyclic carbonates, chain carbonates, cyclic carboxylates, chain carboxylates, etc. are used. As cyclic carbonates, propylene carbonate (PC), ethylene carbonate (EC), vinylene carbonate (VC), etc. can be listed. As chain carbonates, diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), etc. can be listed. In addition, as cyclic carboxylates, γ-butyrolactone (GBL), γ-valerolactone (GVL), etc. can be listed. As chain carboxylates, methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), ethyl propionate (EP), etc. can be listed. The non-aqueous solvent can be used alone or in combination of two or more.
[0029] Examples of the nonaqueous solvent include cyclic ethers, chain ethers, nitriles such as acetonitrile, and amides such as dimethylformamide.
[0030] Examples of the cyclic ether include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, and crown ethers.
[0031] Examples of the chain ethers include 1,2-dimethoxyethane, dimethyl ether, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether.
[0032] These solvents may be fluorinated solvents in which part of hydrogen atoms are replaced by fluorine atoms. As the fluorinated solvent, fluoroethylene carbonate (FEC) can be used.
[0033] As the lithium salt, for example, a lithium salt containing chloric acid (LiClO4, LiAlCl4, LiB 10 Cl 10etc.), lithium salts of fluorinated acids (LiPF6, LiPF2O2, LiBF4, LiSbF6, LiAsF6, LiCF3SO3, LiCF3CO2, etc.), lithium salts of fluorinated imides (LiN(FSO2)2, LiN(CF3SO2)2, LiN(CF3SO2)(C4F9SO2), LiN(C2F5SO2)2, etc.), lithium halides (LiCl, LiBr, LiI, etc.), etc. The lithium salts may be used alone or in combination of two or more.
[0034] The contents of the lithium salt, the cation X, and the oxalate complex anion Y in the electrolyte solution can be measured by, for example, using NMR, ion chromatography, or the like.
[0035] The concentration of the lithium salt in the electrolyte is preferably 1 mol / liter or more and 2 mol / liter or less, more preferably 1 mol / liter or more and 1.5 mol / liter or less. By controlling the lithium salt concentration within the above range, an electrolyte having excellent ion conductivity and moderate viscosity can be obtained. Among them, the lithium salt concentration is not limited to the above. It should be noted that the oxalate complex anion Y can also be added to the electrolyte in the form of a lithium salt. When the oxalate complex anion Y is included, the concentration of the lithium salt refers to: the total concentration of the oxalate complex anion Y and the anions of the lithium salt other than the oxalate complex anion Y (i.e., the lithium ion concentration).
[0036] The concentration of cation X in the electrolyte may also be 0.01 mol / liter or more. In this case, a sufficient capacity retention rate reduction suppression effect can be obtained. The concentration of cation X may also be 0.05 mol / liter or more, or 0.1 mol / liter or more. From the viewpoint of suppressing the reduction of lithium ion conductivity, the concentration of cation X in the electrolyte may also be set to 0.5 mol / liter or less.
[0037] The concentration of the oxalate complex anion Y in the electrolyte may also be 0.01 mol / liter or more. The higher the concentration of the oxalate complex anion Y, the easier it is for the oxalate complex anion Y to be decomposed, and the easier it is for the decomposition to generate gas. From the perspective of suppressing gas generation, the concentration of the oxalate complex anion Y in the electrolyte may also be set to 0.5 mol / liter or less.
[0038] The electrolyte may also contain the aforementioned LiPF6 as a lithium salt. In this case, the molar content of the oxalate complex anion Y may also be adjusted relative to the PF6 contained in the electrolyte. - The ratio of the content of the ions on a molar basis is set to be 0.1 or more and 0.5 or less. By including LiPF6, which is a lithium salt with a high degree of dissociation, at this ratio, sufficient lithium ion conductivity can be obtained as an electrolyte.
[0039] The electrolyte solution may contain other known additives. Examples of the additives include 1,3-propane sultone, toluene sulfonate, cyclohexylbenzene, biphenyl, diphenyl ether, and fluorobenzene.
[0040] [negative electrode]
[0041] The negative electrode, for example, comprises: a negative electrode collector, and a negative electrode active material layer formed on the surface of the negative electrode collector. The negative electrode active material layer can be formed, for example, as follows: a negative electrode slurry in which a negative electrode mixture containing a negative electrode active material, a binder, etc. is dispersed in a dispersion medium is applied to the surface of the negative electrode collector and dried, thereby forming it. The dried coating film can be rolled as needed. That is, the negative electrode active material can also be a mixture layer. In addition, a lithium metal foil or a lithium alloy foil can be attached to the negative electrode collector. The negative electrode active material layer can be formed on one surface of the negative electrode collector, or it can be formed on both surfaces.
[0042] The negative electrode active material layer may contain the negative electrode active material as an essential component, and may contain a binder, a conductive agent, a thickener, etc. as optional components. As the binder, the conductive agent, and the thickener, known materials may be used.
[0043] The negative electrode active material includes: a material that electrochemically absorbs and releases lithium ions, lithium metal, and / or a lithium alloy. As a material that electrochemically absorbs and releases lithium ions, a carbon material, an alloy material, etc. are used. As a carbon material, for example, graphite, easily graphitized carbon (soft carbon), and hardly graphitized carbon (hard carbon) can be exemplified. Among them, graphite with excellent charge and discharge stability and low irreversible capacity is preferred. As an alloy material, at least one metal that can form an alloy with lithium can be listed, and silicon, tin, silicon alloys, tin alloys, silicon compounds, etc. can be listed. Silicon oxide, tin oxide, etc. formed by combining these with oxygen can be used.
[0044] As an alloy material containing silicon, for example, a silicon composite material having a lithium ion conductive phase and silicon particles dispersed in the lithium ion conductive phase can be used. As a lithium ion conductive phase, for example, a silicon oxide phase, a silicate phase and / or a carbon phase can be used. The main component of the silicon oxide phase (for example, 95 to 100% by mass) can be silicon dioxide. Among them, a composite material composed of a silicate phase and silicon particles dispersed in the silicate phase has a high capacity and a small irreversible capacity, and is preferred in this respect.
[0045] The silicate phase may, for example, contain at least one selected from the group consisting of Group 1 elements and Group 2 elements of the long-period type periodic table. As the Group 1 elements of the long-period type periodic table and the Group 2 elements of the long-period type periodic table, for example, lithium (Li), potassium (K), sodium (Na), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), etc. can be used. As other elements, aluminum (Al), boron (B), lanthanum (La), phosphorus (P), zirconium (Zr), titanium (Ti), etc. can be contained. Among them, from the aspect of small irreversible capacity and high initial charge-discharge efficiency, a silicate phase containing lithium (hereinafter also referred to as a lithium silicate phase) is preferred.
[0046] The lithium silicate phase may be an oxide phase containing lithium (Li), silicon (Si), and oxygen (O), and may also contain other elements. The atomic ratio of O to Si in the lithium silicate phase: O / Si is, for example, greater than 2 and less than 4. Preferably, O / Si is greater than 2 and less than 3. The atomic ratio of Li to Si in the lithium silicate phase: Li / Si is, for example, greater than 0 and less than 4. The lithium silicate phase may have a composition represented by the formula: Li 2z SiO 2+z (0 < z < 2). z preferably satisfies the relationship of 0 < z < 1, and more preferably z = 1 / 2. As elements other than Li, Si, and O that can be contained in the lithium silicate phase, for example, iron (Fe), chromium (Cr), nickel (Ni), manganese (Mn), copper (Cu), molybdenum (Mo), zinc (Zn), aluminum (Al), etc. can be cited.
[0047] The carbon phase may, for example, be composed of low-crystallinity amorphous carbon (i.e., Amorphous carbon). The amorphous carbon may be, for example, hard carbon, soft carbon, or others.
[0048] As the negative electrode current collector, a non-porous conductive substrate (such as a metal foil) or a porous conductive substrate (such as a mesh, net, or punched sheet) can be used. As the material of the negative electrode current collector, stainless steel, nickel, nickel alloy, copper, copper alloy, etc. can be exemplified.
[0049] [Positive electrode]
[0050] The positive electrode includes, for example: a positive electrode current collector, and a positive electrode mixture layer formed on the surface of the positive electrode current collector and containing a positive electrode active material. The positive electrode mixture layer can be formed, for example, as follows: a positive electrode paste containing a positive electrode active material, a binder, etc. dispersed in a dispersion medium is coated on the surface of the positive electrode current collector and dried, whereby it can be formed. The dried coating film can be calendered as needed. The positive electrode mixture layer can be formed on one surface of the positive electrode current collector or on both surfaces.
[0051] As the positive electrode active material, for example, the above-mentioned Lia Ni 1-x-y Co x M y O₂ (where 0 < a ≤ 1.2, 0 ≤ x ≤ 0.1, 0 ≤ y ≤ 0.1, 0 < x + y ≤ 0.1, and M is at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Cu, Zn, Al, Cr, Pb, Sb, and B).) The lithium-containing composite oxide shown. From the viewpoint of the stability of the crystal structure, Al can be included as M. As a specific example of such a composite oxide, a lithium-nickel-cobalt-aluminum composite oxide (LiNi 0.9 Co 0.05 Al 0.05 O₂, LiNi 0.91 Co 0.06 Al 0.03 O₂, etc.) can be cited.
[0052] The shape and thickness of the positive electrode current collector can be selected based on the shape and range that match the negative electrode current collector, respectively. As the material of the positive electrode current collector, for example, stainless steel, aluminum, aluminum alloy, titanium, etc. can be exemplified.
[0053] [Separator]
[0054] It is generally desirable to interpose a separator between the positive electrode and the negative electrode. The separator has a high ion permeability and has appropriate mechanical strength and insulation. As the separator, a microporous film, a woven fabric, a non-woven fabric, etc. can be used. As the material of the separator, polyolefins such as polypropylene and polyethylene are preferred.
[0055] As an example of the structure of a non-aqueous electrolyte secondary battery, there can be cited: a structure in which an electrode group formed by winding a positive electrode and a negative electrode with a separator interposed therebetween and a non-aqueous electrolyte are housed in an outer casing. Alternatively, other forms of electrode groups such as a laminated electrode group formed by laminating a positive electrode and a negative electrode with a separator interposed therebetween can be applied instead of the wound electrode group. The non-aqueous electrolyte secondary battery can be in any form such as a cylindrical type, a square type, a coin type, a button type, a laminated type, etc.
[0056] Figure 1 It is a three-dimensional schematic view of a part of a square non-aqueous electrolyte secondary battery according to an embodiment of the present disclosure cut away.
[0057] The battery includes: a bottomed square battery case 11, an electrode group 10 housed in the battery case 11, and a non-aqueous electrolyte (not shown). The electrode group 10 has: a long-sized strip-shaped negative electrode, a long-sized strip-shaped positive electrode, and a separator interposed between them to prevent direct contact. The electrode group 10 can be formed as follows: using a flat-shaped core as the center, winding the negative electrode, the positive electrode, and the separator and removing the core, thereby forming.
[0058] One end of the negative lead 15 is attached to the negative electrode collector of the negative electrode by welding or the like. One end of the positive lead 14 is attached to the positive electrode collector of the positive electrode by welding or the like. The other end of the negative lead 15 is electrically connected to the negative terminal 13 provided on the sealing plate 12. A gasket 16 is arranged between the sealing plate 12 and the negative terminal 13 to insulate the two. The other end of the positive lead 14 is connected to the sealing plate 12 and electrically connected to the battery case 11 which also serves as the positive terminal. A resin frame 18 is arranged on the upper part of the electrode group 10 to separate the electrode group 10 from the sealing plate 12 and to separate the negative lead 15 from the battery case 11. In addition, the opening of the battery case 11 is sealed by the sealing plate 12. An injection hole 17a is formed on the sealing plate 12, and electrolyte is injected into the square battery case 11 from the injection hole 17a. Then, the injection hole 17a is blocked by the sealing plug 17.
[0059] It should be noted that the structure of the non-aqueous electrolyte secondary battery can be cylindrical, coin-shaped, button-shaped, etc. with a metal battery case, or can be a laminated battery with a battery case made of a laminate sheet as a laminate of a barrier layer and a resin sheet. In the present disclosure, the type, shape, etc. of the secondary battery are not particularly limited.
[0060] Hereinafter, the present disclosure will be specifically described based on Examples and Comparative Examples, but the present disclosure is not limited to the following Examples.
[0061] <Example 1>
[0062] [Production of negative electrode]
[0063] Graphite, sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber (SBR), and water as negative electrode active materials were mixed in a predetermined mass ratio to prepare negative electrode slurry. Next, the negative electrode slurry was applied to the surface of copper foil as a negative electrode current collector, and the coating was dried and then rolled to form negative electrode mixture layers on both sides of the copper foil.
[0064] [Production of positive electrode]
[0065] The lithium-containing composite oxide (LiNi 0.9 Co 0.05 Al 0.05 O2), acetylene black, polyvinylidene fluoride, and N-methyl-2-pyrrolidone (NMP) were mixed to prepare positive electrode slurry. Then, the positive electrode slurry was applied on the surface of aluminum foil as a positive electrode collector, and the coating was dried and rolled to form positive electrode mixture layers on both sides of the aluminum foil.
[0066] [Preparation of non-aqueous electrolyte]
[0067] A non-aqueous electrolyte was prepared by adding LiPF6 as a lithium salt and cesium difluorooxalatoborate (CsBF2(C2O4)) as a salt of a cation X and an oxalate complex anion Y to a mixed solvent containing fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), and dimethyl ether (DME) in a volume ratio of 4:1:15. The concentration of LiPF6 in the non-aqueous electrolyte was 1.0 mol / liter. The concentration of CsBF2(C2O4) in the non-aqueous electrolyte was 0.1 mol / liter.
[0068] [Fabrication of non-aqueous electrolyte secondary battery]
[0069] Lead tabs were installed on each electrode, and the positive electrode and the negative electrode were wound into a spiral shape with the separator sandwiched so that the lead was located at the outermost periphery, thereby preparing an electrode group. The electrode group was inserted into an outer casing made of a laminated film with aluminum foil as a barrier layer, and after vacuum drying at 105°C for 2 hours, a non-aqueous electrolyte was injected, and the opening of the outer casing was sealed to obtain a battery A1.
[0070] <Example 2>
[0071] In the preparation of the non-aqueous electrolyte, magnesium difluorooxalatoborate (Mg(BF2(C2O4))2) was used instead of CsBF2(C2O4). The concentration of Mg(BF2(C2O4))2 in the non-aqueous electrolyte was 0.1 mol / liter.
[0072] A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1 except for the above, thereby obtaining Battery A2.
[0073] <Comparative Example 1>
[0074] In the preparation of the non-aqueous electrolyte, no CsBF2 (C2O4) was added.
[0075] A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1 except for the above, thereby obtaining Battery B1.
[0076] <Comparative Example 2>
[0077] For lithium-containing composite oxides used as positive electrode active materials, LiNi 0.8 Co 0.15 Al 0.05 O2.
[0078] In addition, CsBF2 (C2O4) was not added in the preparation of the non-aqueous electrolyte.
[0079] A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1 except for the above, thereby obtaining Battery B2.
[0080] <Comparative Example 3>
[0081] For lithium-containing composite oxides used as positive electrode active materials, LiNi 0.8 Co 0.15 Al 0.05 O2.
[0082] A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1 except for the above, thereby obtaining Battery B3.
[0083] <Comparative Example 4>
[0084] For lithium-containing composite oxides used as positive electrode active materials, LiNi 0.8 Co 0.15 Al 0.05 O2.
[0085] A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 2 except for the above, thereby obtaining Battery B4.
[0086] [evaluate]
[0087] (Initial charge and discharge)
[0088] Each completed battery was placed in an environment of 25°C and charged at a constant current of 0.3 It until the voltage reached 4.1 V, and then charged at a constant voltage of 4.1 V until the current reached 0.02 It. Then, the battery was discharged at a constant current of 0.3 It until the voltage reached 2.85 V, and the initial discharge capacity C0 was obtained. The charging and discharging was performed in an environment of 25°C.
[0089] (Capacity maintenance rate)
[0090] The pause period between charge and discharge was 10 minutes. The charge and discharge conditions were repeated 100 times at 25°C, and the discharge capacity C1 at the 100th cycle was calculated. The ratio of the discharge capacity C1 to the initial discharge capacity C0 (R1=C1 / C0) was evaluated as the capacity retention rate.
[0091] Table 1 shows the evaluation results of the initial discharge capacity C0 and the capacity retention rate R1 of batteries A1, A2, B1 to B4. Table 1 also shows the positive electrode active material and additives used in each battery. According to Table 1, compared with batteries B1 to B4, batteries A1 and A2 have excellent initial discharge capacity C0 and high capacity retention rate R1.
[0092] Battery B1 has a low ratio of cobalt and a high ratio of nickel in the lithium-containing composite oxide, so the capacity retention rate R1 is significantly reduced compared to Battery B2. On the other hand, Batteries B2 to B4 have a high ratio of cobalt and a low ratio of nickel in the lithium-containing composite oxide, so the initial discharge capacity C0 is small.
[0093] In batteries B2 to B4, the improvement effect of the capacity maintenance rate R1 brought about by the addition of cation X and oxalate complex anion Y to the electrolyte was not observed, and the capacity maintenance rate R1 decreased due to the addition of cation X and oxalate complex anion Y. In contrast, in batteries A1 and A2, the capacity maintenance rate R1 was greatly improved compared with battery B1 by adding cation X and oxalate complex anion Y to the electrolyte.
[0094] [Table 1]
[0095]
[0096] Industrial Applicability
[0097] According to the nonaqueous electrolyte secondary battery of the present disclosure, a nonaqueous electrolyte secondary battery with high capacity and reduced cobalt usage can be provided. The nonaqueous electrolyte secondary battery of the present disclosure is useful as a main power source for mobile communication devices, portable electronic devices, and the like.
[0098] Description of Reference Numerals
[0099] 1 Non-aqueous electrolyte secondary battery
[0100] 10 Electrode Group
[0101] 11 Battery housing
[0102] 12 Sealing plate
[0103] 13 Negative terminal
[0104] 14 Positive lead
[0105] 15 Negative lead
[0106] 16 Gasket
[0107] 17 Sealing plug
[0108] 17a Filling hole
[0109] 18 Frame
Claims
1. A non-aqueous electrolyte secondary battery, comprising: a positive electrode, a separator, a negative electrode facing the positive electrode with the separator interposed therebetween, and an electrolytic solution. The positive electrode contains a composite oxide, and the composite oxide contains lithium as a first metal and a second metal other than lithium. In the composite oxide, the second metal contains Ni, the proportion of Ni in the second metal is 90 atomic% or more, and the proportion of Co in the second metal is 10 atomic% or less. The electrolyte comprises: selected from Rb + , Cs + 、Fr + , Sr 2+ , and Ba 2+ At least one cation X in the group consisting of; and an oxalate complex anion Y, The electrolyte contains PF6 - ion, The molar content of the oxalate complex anion Y in the electrolyte relative to the PF6 - The molar content ratio of the ions is 0.1 or more and 0.5 or less, The composite oxide comprises a composition formula of Li a Ni 1-x-y Co x M y O2 is a material, wherein 0 < a ≤ 1.2, 0 ≤ x ≤ 0.1, 0 ≤ y ≤ 0.1, 0 < x + y ≤ 0.1, and M is at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Cu, Zn, Al, Cr, Pb, Sb, and B.
2. The nonaqueous electrolyte secondary battery according to claim 1, wherein The cation X comprises Cs + .
3. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: The oxalate complex anion Y comprises a compound selected from B(C2O4)2 - 、BF2(C2O4) - 、P(C2O4)3 - PF2(C2O4)2 - , and PF4(C2O4) - At least one of the group consisting of.
4. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: The oxalate complex anion Y contains fluorine.
5. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: The concentration of the oxalate complex anion Y in the electrolytic solution is 0.5 mol / L or less.
6. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: The concentration of the cation X in the electrolytic solution is 0.01 mol / L or more and 0.5 mol / L or less.
7. The nonaqueous electrolyte secondary battery according to claim 1, wherein The M contains Al.
8. The nonaqueous electrolyte secondary battery according to claim 1, wherein The composite oxide satisfies 0 < x ≤ 0.05.
Citation Information
Patent Citations
Nonaqueous electrolyte and lithium ion secondary battery including the same
JP2016139610A
Non-aqueous electrolyte solution and non-aqueous electrolyte solution secondary battery using the same
CN103762381A
Non-aqueous electrolyte secondary battery
CN109937504A